Eigenvalues of K-invariant Toeplitz Operators on Bounded Symmetric Domains - Upmeier, Harald (Integral equations and operator theory, 2021)
We determine the eigenvalues of certain “fundamental” K -invariant Toeplitz type operators on weighted Bergman spaces over bounded symmetric domains D = G / K , for the irreducible K -types indexed by all partitions of length r = rank ( D ) .